Pembelajaran Pendidikan Agama Islam Berbasis Diferensiasi Gaya Belajar Siswa Kelas IX di SMP Negeri 7 Padang - Elcery, Melinnia; Satria, Rengga (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The background of this research is because there are differences in learning styles that each student has, so a teacher must have expertise in managing learning based on student learning styles. This study aims to find out how Islamic Religious Education teachers map the learning styles of class IX students, how do Religious Education teachers accommodate the 3 learning styles of class IX students and what are the constraints and solutions of Islamic Religious Education teachers in accommodating the 3 learning styles of class IX in Padang 7 Public Middle School. Research using descriptive qualitative method. Sources of data were taken from primary data sources, namely interviews with Islamic Religious Education teachers of class IX, and secondary data, namely the results of interviews with school principals, students of class IX-3 and other supporting documents. The informants interviewed included one school principal, one Islamic Religious Education teacher for class IX, and five students for class IX-3. To obtain research data, researchers used a set of interview guidelines and observation guidelines as research instruments. Data collection techniques used in this research are observation, interviews and documentation. Meanwhile the data analysis techniques used are data collection, data reduction, data presentation and conclusion. The results showed that the way the Islamic Religious Education teacher mapped the learning styles of class IX students was through the results of the mapping carried out by the Counseling Guidance (BK) section, the way the Islamic Religious Education teacher accommodated the 3 learning styles of students IX was by carrying out various learning in each meeting, the obstacles and solutions faced by Islamic Religious Education teachers in accommodating the 3 learning styles of class IX students, namely the standard existing facilities and teaching time that feels short so that the solution taken is to maximize the time available while still trying to meet each style's needs student learning.